1993
DOI: 10.1002/jat.2550130210
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and pulmonary irritation of aliphatic amines in mice: A structure–activity relationship study

Abstract: The expiratory bradypnea indicative of upper airway irritation in mice was evaluated during a 15-min oronasal exposure to increasing concentrations of sixteen aliphatic amines. The airborne concentration resulting in a 50% decrease in the respiratory rate of mice (RD50) was calculated for each test compound. Moreover, the sixteen amines were tested for pulmonary irritation by measuring the decrease in respiratory rate of (non-anaesthetized) tracheally cannulated mice (RD50 TC). The RD50 and RD50 TC values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 212 The Expert Panel determined to not reopen this safety assessment and confirmed that diisopropylamine is safe as a cosmetic ingredient when used in products that do not contain N -nitrosating agents.…”
Section: Resultsmentioning
confidence: 99%
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 212 The Expert Panel determined to not reopen this safety assessment and confirmed that diisopropylamine is safe as a cosmetic ingredient when used in products that do not contain N -nitrosating agents.…”
Section: Resultsmentioning
confidence: 99%
“…Nielsen and co-workers (44) correlated log RD 50 values against log K for solubility of gaseous compounds in wet octanol, but only for a restricted set of VOCs, and also used the water to octanol partition coefficient, as log Poct, as a descriptor; other workers did likewise (45), again for a very restricted set of VOCs. The meaning of the six descriptors is given in Table 2.…”
Section: Upper Respiratory Tract Irritation In Micementioning
confidence: 99%